PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMSÂ ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR PASSING BAWAH BOLAVOLI (STUDI PADA SISWA KELAS X SMAN 1 SUKAPURA, PROBOLINGGO) - PURNOMO, PUJIANTO (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Penjasorkes contains elements that are important values ??in life. Value of cooperation is one of the values ??that exist in Penjasorkes and needed and used in public life is harmonious and dignified.  One of the teaching material that contains the value of cooperation in the Penjasorkes is a game of volleyball.  This study is motivated by the lack of student mastery of passing down techniques that result in passing the ball down is often not directed to the opponent misses the intended and most often fight among players in doing passing down due to lack of cooperation among players. Formulation of the problem posed in this study is whether there is influence STAD cooperative learning model to study the results of passing under the volleyball in class X SMAN 1 Sukapura, Probolinggo and how big influence. The purpose of this study was to determine the effect of STAD cooperative learning model to the results of passing under the volleyball in class X SMAN 1 Sukapura, Probolinggo and to determine the magnitude of the effect. Cooperative learning model Student Teams Achievement Division (STAD) is a model of learning by students are grouped in teams of 4-6 members. With the implementation of cooperative learning model STAD expected learning outcomes of students passing increased under volleyball. This research is descriptive quantitative approach to experiment. The samples in this study were 48 students, consisting of 22 students XA class as the experimental group and 26 students XC class as the control group. Results of the study were independent t test can be concluded that there is a significant relationship between STAD cooperative learning model to learning outcomes as evidenced volleyball passing down of the value of t = 3.688 is greater than the value of t table (3.688> 1.6775) with a significance level of 0 , 05. The amount of influence STAD cooperative learning model to the learning outcomes of students passing class X under SMAN 1 Sukapura, Probolinggo is equal to 13.86%. Keywords: STAD cooperative learning model, volleyball underhand pass, learning outcomes.